2020
DOI: 10.29138/ijebd.v3i4.1200
|View full text |Cite
|
Sign up to set email alerts
|

The Use of E-Learning in Maritime English Learning Can Improve the Vocabulary Skill of Cadets Majoring in Electro-Technical Officer Shipping

Abstract: Purpose: The increasingly global trade in the world demands the sea transportation industry, especially ships, to further increase the capabilities and expertise of the crew, especially the ability to communicate in English. So in the national education system, learning English is very important.  . Design/methodology/approach: Various methods are used to improve English language skills, one of which is the use of technology in learning for students, namely by using e-learning. Findings: This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Besides, students and instructors reported that student officers had trouble understanding written instructions for routine shipboard activities (Erawati, 2014). Observations from multiple meetings and a study pre-test of Maritime English learning revealed many obstacles, including a lack of ship electrical terminology vocabulary (Sukomardojo & Ratnaningsih, 2020). Some studies have found that seafarers need to improve their maritime English, but they should also be assessed for general English proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, students and instructors reported that student officers had trouble understanding written instructions for routine shipboard activities (Erawati, 2014). Observations from multiple meetings and a study pre-test of Maritime English learning revealed many obstacles, including a lack of ship electrical terminology vocabulary (Sukomardojo & Ratnaningsih, 2020). Some studies have found that seafarers need to improve their maritime English, but they should also be assessed for general English proficiency.…”
Section: Introductionmentioning
confidence: 99%